Histological Alterations in Bronchial Epithelium and Serum IgE in Bronchial Asthma - Saira Aslam, Uzma Hanif, Sadia Saqib, Ahmad Farzad Qureshi, Amrat, Kanwal Khalid, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A prospective cross-sectional study assessed histological alterations in bronchial epithelium andtheir correlation with serum total IgE in 120 adult patients with bronchial asthma compared to 60healthy controls. Bronchial biopsies obtained via bronchoscopy were evaluated for epithelialshedding, goblet cell hyperplasia